20 Myocardial extracellular volume predicts functional recovery in acute myocardial infarction more accurately than threshold-based measures of late gadolinium enhancement transmural extent. (26th April 2015) - Kidambi, A; Motwani, M; Uddin, A; Ripley, DP; McDiarmid, AK; Swoboda, PP; Broadbent, DA; Musa, TA; Erhayiem, B; Greenwood, JP; Plein, S
Abstract : The transmural extent of late gadolinium enhancement (LGE) CMR predicts functional recovery in acute myocardial infarction (AMI). Automated methods are recommended 1 to define infarct extent on LGE imaging, such as 'n-standard deviations' (SD) and 'full width at half maximum' (FWHM). These define infarcted myocardium by signal intensity as compared to remote myocardium, which in turn depends on signal-to-noise and contrast. Individual variability in these parameters makes a single thresholding technique unlikely to be universally suitable. Extracellular volume (ECV) estimation by T1-mapping CMR is theoretically less affected by sequence and contrast variations. We compared infarct ECV with threshold-based measures of LGE transmural extent to predict contractile recovery in reperfused AMI. Consecutive patients with reperfused first ST-elevation AMI underwent acute (day 2) and convalescent (3 months) CMR. Cine imaging, modified Look-Locker inversion T1 mapping natively and 15 min post gadolinium-contrast administration and LGE imaging were performed. Five LGE thresholding techniques were compared: 2, 5 and 6 SD, FWHM and a histogram-based technique (Otsu). 2 The ability of acute infarct ECV to predict improvement in segmental wall motion was compared with these thresholding techniques. n = 35 (28(80%) male, age 57 ± 11 years). Infarct characteristics are shown in Table 1. ECV showed modest correlation with all threshold measures of LGE (r 2 = 0.16–0.31, p < 0.01). Reduced convalescent wall motion score correlated with acute ECV (p < 0.01), and acute LGE for 5 SD (p < 0.01), 6 SD (p < 0.01) and FWHM (p = 0.01), but not 2 SD (p = 0.2) or Otsu (p = 0.6). Acute infarct ECV demonstrated a significantly higher c-statistic for prediction of improved segmental convalescent wall motion score than all threshold measures of acute transmural LGE extent (p ≤ 0.02 for all, Figure 1 ). Acute infarct ECV outperforms threshold-based LGE transmural extent to predict segmental LV functional recovery in reperfused AMI. References: Schulz-Menger J, et al . J Card Magn Reson 2013;15:35 Otsu N. IEEE Trans Sys Man Cyber. 1979;9:62–6